SPSS for Windows Made Simple / Release 10: Also suitable for SPSS II - Gray Colin D; Kinnear Paul R (Psychology Press, 2000)
Preface, Choosing a Statistical Test, Windows Operations for SPSS, Data Handling in SPSS, Exploratory Data Analysis, More Graphs and Charts, Comparing Averages: Two Sample and One-Sample, The One-Factor Between Subjects Experiment, Factorial Experiments (Between Subjects), Within Subjects Experiments, Experiments of Mixed Design, Measuring Statistical Association, Regression, Multiway Frequency Analysis, Discriminant Analysis and Logistic Regression, Factor Analysis, Revision Exercises, References, Index.